2021
DOI: 10.1007/s10461-021-03201-3
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Coping, and Social Support Among People Living with HIV in the Americas: A Comparative Study Between Argentina and the USA During the SARS-CoV-2 Pandemic

Abstract: The COVID-19 pandemic poses a risk to mental health and may disproportionately affect people living with HIV (PLWH). This study examined the interaction of social support and resilient coping in predicting depressive symptoms among PLWH. PLWH residing in Buenos Aires, Argentina and in Miami, Florida (US) were asked to complete an anonymous survey on the impact of COVID-19. Statistical analysis included ordinary least squares regression. A total of 1,554 participants were included. Mean age was 47.30 years; 63.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…isolating self) that increased during the pandemic (Additional File 3). Another study similarly reported that higher levels of social support and resilient coping were associated with lower depressive symptoms among adults with HIV in the context of the COVID-19 pandemic (50). The increase in social isolation (spending less time with support networks, less time going out or spending time with others, and tending to isolate self more), a likely consequence of the COVID-19 restrictions, aligns with the increase in disability in dimensions of social inclusion and mental-emotional health as measured by the HDQ.…”
Section: Discussionmentioning
confidence: 96%
“…isolating self) that increased during the pandemic (Additional File 3). Another study similarly reported that higher levels of social support and resilient coping were associated with lower depressive symptoms among adults with HIV in the context of the COVID-19 pandemic (50). The increase in social isolation (spending less time with support networks, less time going out or spending time with others, and tending to isolate self more), a likely consequence of the COVID-19 restrictions, aligns with the increase in disability in dimensions of social inclusion and mental-emotional health as measured by the HDQ.…”
Section: Discussionmentioning
confidence: 96%
“…The majority of participants reported sustained use of positive living strategies during the pandemic with the exception of positive social interaction strategies and negative strategies (e.g., isolating self) that increased during the pandemic (Additional file 3 ). Another study similarly reported that higher levels of social support and resilient coping were associated with lower depressive symptoms among adults with HIV in the context of the COVID-19 pandemic [ 50 ]. The increase in social isolation (spending less time with support networks, less time going out or spending time with others, and tending to isolate self more), a likely consequence of the COVID-19 restrictions, aligns with the increase in disability in dimensions of social inclusion and mental-emotional health as measured by the HDQ.…”
Section: Discussionmentioning
confidence: 99%
“…Among US African-American women, resilience correlated significantly to medication adherence ( 33 ). Outside of the US, depression and resilience were correlated inversely, among South African women (99% of Black race) ( 37 ), and Latin American men and women ( 38 ).…”
Section: Discussionmentioning
confidence: 99%